Student learning focus in the application of mindful learning in the digital age - Nilia Wati; Wistina Seneru; Sutiyono Sutiyono (Universitas Sebelas Maret, 2025)
Education plays a very important role in shaping character and improving the quality of the learning process, especially amid the challenges of the digital age, which is full of distractions. This study aims to determine the effect of mindful learning on students' learning focus. For example, the issues identified among students include a decline in their ability to maintain focus during learning, high levels of distraction due to the use of digital devices, and low levels of active student participation in class. This study is expected to provide solutions to improve students' focus in order to create a more comfortable and productive learning atmosphere. Mindful learning, which involves learning activities through the practice of samatha Bhavana (meditation for inner peace), can have a positive impact on students' focus on learning. Through learning experiences that emphasize mindfulness, students are gradually trained to manage their attention better, reduce distractions, and increase concentration and active participation in the learning process. This study used a survey method with a quantitative approach. Data collection techniques were carried out through a questionnaire with a Likert scale. The study population included all eighth-grade students, with a sample size of 51 students selected at random. Simple linear regression analysis was used to test the research hypothesis, with the help of SPSS version 27 software to analyze the data. The results showed that mindful learning had a positive and significant effect on students' learning focus. These findings confirm that the practice of mindful learning, particularly through the Samatha Bhāvanā method (meditation for inner peace), can improve students' concentration and active participation in the learning process. Therefore, the integration of mindful learning into the learning process is highly recommended in order to create a more comfortable, conducive, and productive learning atmosphere.